Pembiasaan Nilai-Nilai Islami dan Keteladanan Guru dalam Mengembangkan Karakter Peserta Didik - Yunani, Yuyun; Sumadi, Sumadi (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2016)
The purpose of this study was to understand the interrelationships between habituation of Islamic values, exemplary teachers, and the character of the students. The results show that habituation of Islamic values in SMP Negeri 2 Ciamis done inside and outside of instructional hours that includes the values of faith, morals, worship. The process of habituation was getting stronger when supported by exemplary teachers. The character development of students include the development of religiosity, honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity, the spirit of nationalism, patriotism, recognize excellence, communicative, love peace, love reading, environmental care, social care , and responsibility.